Load and performance monitoring in wheelchair court sports: A narrative review of the use of technology and practical recommendations - van der Slikke, R. M.; Sindall, P.; Goosey-Tolfrey, V. L.; Mason, B. S. (European Journal of Sport Science, 2023)
Quantifying measures of physical loading has been an essential part of performance monitoring within elite able-bodied sport, facilitated through advancing innovative technology. In wheelchair court sports (WCS) the inter-individual variability of physical impairments in the athletes increases the necessity for accurate load and performance measurements, while at the same time standard load monitoring methods (e.g. heart-rate) often fail in this group and dedicated WCS performance measurement methods are scarce. The objective of this review was to provide practitioners and researchers with an overview and recommendations to underpin the selection of suitable technologies for a variety of load and performance monitoring purposes specific to WCS. This review explored the different technologies that have been used for load and performance monitoring in WCS. During structured field testing, magnetic switch-based devices, optical encoders and laser systems have all been used to monitor linear aspects of performance. However, movement in WCS is multidirectional, hence accelerations, decelerations and rotational performance and their impact on physiological responses and determination of skill level, is also of interest. Subsequently both for structured field testing as well as match-play and training, inertial measurement units mounted on wheels and frame have emerged as an accurate and practical option for quantifying linear and non-linear movements. In conclusion, each method has its place in load and performance measurement, yet inertial sensors seem most versatile and accurate. However, to add context to load and performance metrics, position-based acquisition devices such as automated image-based processing or local positioning systems are required.